Tracking Control of Ball Screw Drives Using ADRC and Equivalent-Error-Model-Based Feedforward Control - Zhang, Chengyong; Chen, Yaolong (IEEE transactions on industrial electronics (1982), 2016)
This paper proposes a novel disturbance-rejection tracking controller for ball screw feed drives. First, active-disturbance-rejection control (ADRC) and proportional-integral (PI) control are employed to ensure the performance of the closed-loop system. In this control framework, the extended state observer estimates and compensates for unmodeled dynamics, parameter perturbations, variable cutting load, and other uncertainties, which improves the disturbance-rejection performance and robustness of the system. Then, based on ADRC feedback linearization, a novel equivalent-error-model-based feedforward controller is designed to further improve the tracking performance of the system. This equivalent error model is independent of the mechanical model, simple to design and easy to tune. Simulations and experimental results demonstrate that the proposed control method has better tracking performance and robustness against the internal and external disturbances compared with the conventional P-PI controller.